PMRI Learning With Blended Learning Strategy to Improve Mathematical Literacy Skill - Dianawati, Rizki Nur; Wardono, Wardono; Kartono, Kartono (Unnes Journal of Mathematics Education Research, 2018)
The mathematics literacy of students in State Junior High School 5 Semarang is still low. Students face difficulties when they are solving stories related to daily life. The objective of this study is to determine the effectiveness of PMRI learning assessed similarly to PISA with Blended Learning strategy towards students' mathematical literacy skills. The learning includes face-to-face activities and the use of computer technology (online or offline). The population in this study was the students of VIII graders of State Junior High School 5 Semarang in the academic year of 2015/2016. This research used quantitative method. The sample was chosen by random sampling and it was obtained class og VIII E, VIII F, and VIII G as experiment and control classes. The data were obtained by mathematical literacy skill test method. The data analysis used was proportion test, Anova test and Gain test. The results show that (1) the average of mathematics literacy skill on the PMRI learning with Blended Learning has reached the classical completeness that is at least 75% of students reach a minimum score of 70; (2) the average of mathematics literacy skill of class with PMRI learning with Blended Learning is better than class with expository learning.